Construction and Immunogenicity of DNA Vaccines Encoding Fusion Protein of Porcine IFN-λ1 and GP5 Gene of Porcine Reproductive and Respiratory Syndrome Virus. (24th December 2013) - Du, Luping; Li, Bin; He, Kongwang; Zhang, Haibin; Huang, Kehe; Xiao, Shaobo
Abstract : Porcine reproductive and respiratory syndrome virus (PRRSV) has been mainly responsible for the catastrophic economic losses in pig industry worldwide. The commercial vaccines only provide a limited protection against PRRSV infection. Thus, the focus and direction is to develop safer and more effective vaccines in the research field of PRRS. The immune modulators are being considered to enhance the effectiveness of PRRSV vaccines. IFN- λ 1 belongs to type III interferon, a new interferon family. IFN- λ 1 is an important cytokine with multiple functions in innate and acquired immunity. In this study, porcine IFN- λ 1 (PoIFN- λ 1) was evaluated for its adjuvant effects on the immunity of a DNA vaccine carrying the GP5 gene of PRRSV. Groups of mice were immunized twice at 2-week interval with 100  μ g of the plasmid DNA vaccine pcDNA3.1-SynORF5, pcDNA3.1-PoIFN- λ 1-SynORF5, and the blank vector pcDNA3.1, respectively. The results showed that pcDNA3.1-PoIFN- λ 1-SynORF5 can significantly enhance GP5-specific ELISA antibody, PRRSV-specific neutralizing antibody, IFN- γ level, and lymphocyte proliferation ratherthan the responses induced by pcDNA3.1-SynORF5. Therefore, type III interferon PoIFN- λ 1 could enhance the immune responses of DNA vaccine of PRRSV, highlighting the potential value of PoIFN- λ 1 as a molecular adjuvant in the prevention of PRRSV infection.